High-sensitive and rapid detection of Mycobacterium tuberculosis infection by IFN-γ release assay among HIV-infected individuals in BCG-vaccinated area - Jiang Weimin (BMC Immunology, 2009)
Abstract Background An accurate test for Mycobacterium tuberculosis infection is urgently needed in immunosuppressed populations. The aim of this study was to investigate the diagnostic power of enzyme-linked immunospot (ELISPOT)-based IFN-γ release assay in detecting active and latent tuberculosis in HIV-infected population in bacillus Calmette-Guerin (BCG)-vaccinated area. A total of 100 HIV-infected individuals including 32 active tuberculosis patients were recruited. An ELISPOT-based IFN-γ release assay, T-SPOT.TB, was used to evaluate the M. tuberculosis ESAT-6 and CFP-10 specific IFN-γ response. Tuberculin skin test (TST) was performed for all recruited subjects. Results The subjects were divided into group HIV+ATB (HIV-infected individuals with active tuberculosis, n = 32), group HIV+LTB (HIV-infected individuals with positive results of T-SPOT.TB assay, n = 46) and group HIV only (HIV-infected individuals with negative results of T-SPOT.TB assay and without evidence of tuberculosis infection, n = 22). In group HIV+ATB and HIV+LTB, T-SPOT.TB positive rate in subjects with TST <5 mm were 50% (16/32) and 41.3% (19/46), respectively. Individuals in group HIV+ATB and HIV+LTB with CD4+ T cells <500/μl, T-SPOT.TB showed a higher sensitivity than TST (64.5% vs. 22.6% and 62.2% vs. 29.7%, respectively, both P < 0.0001). In addition, the sensitivity of T-SPOT.TB assay in group HIV+ATB increased to >85% in patients with TB treatment for less than 1 month and CD4+ T cells ≥200/μl, while for patients treated for more than 3 months and CD4+ T cells <200/μl, the sensitivity was decreased to only 33.3%. Furthermore, the results could be generated by T-SPOT.TB assay within 24 hours, which was more rapid than TST with 48–72 hours. Conclusion ELISPOT-based IFN-γ release assay is more sensitive and rapid for the diagnosis of TB infection in Chinese HIV-infected individuals with history of BCG vaccination, and could be an effective tool for guiding preventive treatment with isoniazid in latently infected people and for TB control in China.